Humans with latent toxoplasmosis display altered reward modulation of cognitive control - Stock, Ann-Kathrin; Dajkic, Danica; Köhling, Hedda Luise; von Heinegg, Evelyn Heintschel; Fiedler, Melanie; Beste, Christian (Scientific reports, 2017)
Latent infection with Toxoplasma gondii has repeatedly been shown to be associated with behavioral changes that are commonly attributed to a presumed increase in dopaminergic signaling. Yet, virtually nothing is known about its effects on dopamine-driven reward processing. We therefore assessed behavior and event-related potentials in individuals with vs. without latent toxoplasmosis performing a rewarded control task. The data show that otherwise healthy young adults with latent toxoplasmosis show a greatly diminished response to monetary rewards as compared to their non-infected counterparts. While this selective effect eliminated a toxoplasmosis-induced speed advantage previously observed for non-rewarded behavior, Toxo-positive subjects could still be demonstrated to be superior to Toxo-negative subjects with respect to response accuracy. Event-related potential (ERP) and source localization analyses revealed that this advantage during rewarded behavior was based on increased allocation of processing resources reflected by larger visual late positive component (LPC) amplitudes and associated activity changes in the right temporo-parietal junction (BA40) and left auditory cortex (BA41). Taken together, individuals with latent toxoplasmosis show superior behavioral performance in challenging cognitive control situations but may at the same time have a reduced sensitivity towards motivational effects of rewards, which might be explained by the presumed increase in dopamine.
Keywords: dopamin; Auditory Cortex; Humans; Case-Control Studies; toxoplazmóza; evokované potenciály; kognice; studie případů a kontrol; Female; Toxoplasmosis; mladý dospělý; dospělí; lidé; Adult; ženské pohlaví; Toxoplasma; Male; Evoked Potentials; protilátky protozoální; Dopamine; Young Adult; Antibodies, Protozoan; mužské pohlaví; Cognition; Reward; sluchové korové centrum; odměna